Allogeneic hematopoietic stem cell transplant overcomes poor prognosis of acute myeloid leukemia with myelodysplasia-related changes. Issue 1 (2nd January 2016) - Ikegawa, Shuntaro; Doki, Noriko; Kurosawa, Shuhei; Yamaguchi, Tsukasa; Sakaguchi, Masahiro; Harada, Kaito; Yamamoto, Keita; Hino, Yutaro; Shingai, Naoki; Senoo, Yasushi; Watanabe, Ken; Igarashi, Aiko; et al.
Abstract : Recent studies have shown that acute myeloid leukemia with myelodysplasia-related changes (AML-MRC) exhibits a worse clinical outcome than AML not otherwise specified (AML-NOS). However, transplant outcomes of patients with AML-MRC have not been reported compared to patients with AML-NOS. We analyzed transplant outcomes among 147 patients with AML-MRC or AML-NOS who underwent allogeneic hematopoietic stem cell transplant (allo-HSCT) in a single institution. There were no significant differences in the 2-year overall survival (OS), cumulative incidence of relapse (CIR), and non-relapse mortality (NRM) between the two groups (2-year OS: 48% vs. 59%; 2-year CIR: 37% vs. 35%; 2-year NRM: 19% vs. 13%). Subgroup analysis adjusting for age and disease status demonstrated the same results between the two groups. Furthermore, multivariate analysis showed that AML-MRC was not an independent prognostic factor for poor prognosis in the setting of allo-HSCT ( p = 0.7). These results suggest that allo-HSCT may overcome the poor prognosis of AML-MRC.